# Difference between revisions of "P. 265, Equation (7.16)"

From Bill Goodwine's Wiki

Jump to navigationJump to search (Created page with "The equation should be <math></math>") |
|||

Line 1: | Line 1: | ||

− | The | + | The second line should be |

− | <math></math> | + | <math>=-\lambda \left[ -\lambda \left( \lambda^2 - \lambda k_4 + 1 - k_3 \right) + k_2 \right] - \left[ -2 \left( \lambda^2 - \lambda k_4 + 1 - k_3 \right) - k_1 -1 \right]</math> |

+ | |||

+ | The third line should be: | ||

+ | |||

+ | <math>= \lambda^4 - k_4 \lambda^3 + \left( 3 - k_3 \right) \lambda^2 - \left(2 k_4 + k_2 \right) \lambda + \left(1 - k_1 - 2 k_3 \right) = 0.</math> |

## Revision as of 13:57, 16 April 2012

The second line should be

The third line should be: